Christmas in the Quran or Night of Determination? An interpretation of Surah 97 - Sinai, N (2012)
This article proposes to interpret Surah 97 based on research undertaken in the framework of the Corpus Coranicum, project. The first part scrutinizes Christopn LUXENBERG'S seriously flawed argument that Surah 97 can be understood as a Qur'anic hymn on the Nativity of Jesus if some of its key expressions are read against the semantic background of Syriac, while the remainder of the article endeavours to develop a more tenable understanding of the text. This involves an attempt to date Surah 97 relative to other Qur'anic texts and to detect possible additions to it. In addition, the article discusses the meaning and reference of its most central term, laylat al-qadr. Finally special attention is given to the question whether the text might not, in spite of the circularity of LUXENBERG'S reading, contain implicit references to the Nativity. © Walter de Gruyter 2012.